2019
DOI: 10.1007/s10344-019-1284-4
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preferences in dry season of the Italian hare (Lepus corsicanus) in two sites of Corsica

Abstract: In this research, the diet composition and feeding selection of the Italian hare were evaluated and compared in two sites of Haute-Corse region localised in the territories of Tallone and Aleria. The present study is the first considering feeding selection of Lepus corsicanus. The considered period ranged from June to October. Quadrat method was used to assess plant frequency, while diet composition was determined by microhistological analysis of faecal pellets collected monthly. Grasses represented the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…On the contrary, in Sicily, the Italian hare is relatively widespread and is also observed in hunting areas far from protected parks. In Corsica, the presence of the species is evidenced in Haute-Corse and on the coastal area of Sagone, where the species is threatened by hybridization with L. europaeus, and with the Iberian hare (Lepus granatensis Rosenhauer, 1856) [3,4]. The species occupies mainly Mediterranean environments, even if it has been observed up to altitudes close to 2000 m [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in Sicily, the Italian hare is relatively widespread and is also observed in hunting areas far from protected parks. In Corsica, the presence of the species is evidenced in Haute-Corse and on the coastal area of Sagone, where the species is threatened by hybridization with L. europaeus, and with the Iberian hare (Lepus granatensis Rosenhauer, 1856) [3,4]. The species occupies mainly Mediterranean environments, even if it has been observed up to altitudes close to 2000 m [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the plants composing the diet may act as early warning indicators of food resource limitation, especially concerning diet overlap with other animals [7]. Studies on diet composition of the species, carried out in Sicily [8], Corsica [4], and in peninsular Italy [9][10][11][12][13], demonstrated that the Italian hare feeds on a large number of species of plants during the year, with a conspicuous presence of herbaceous ones (e.g., B. sylvaticum, Trifolium pratense, Lolium arundinaceum). Grasses and non-leguminous forbs represent the basis of the diet, with a higher incidence of Poaceae, Fabaceae, and Asteraceae in summer and of Rosaceae, Fagaceae, and Pinaceae (leaves, buds and barks) in the winter period [4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Data on the plant species identified in DS and WS were used to calculate the relative frequencies of each taxon, family, and vegetation form. Similarly, we calculated the relative frequencies of the plant species identified in the feces by dividing the total number of fragments attributed to a given taxon by the total number of identified fragments collected for each season [27][28][29]. Data on identified plant species composing the diet were also used to compute the following alpha diversity indices:…”
Section: Discussionmentioning
confidence: 99%
“…Data on the plant species identified in DS and WS were used to calculate the relative frequencies of each taxon, family, and vegetation form. Similarly, we calculated the relative frequencies of the plant species identified in the feces by dividing the total number of fragments attributed to a given taxon by the total number of identified fragments collected for each season [ 27 , 28 , 29 ]. Data on identified plant species composing the diet were also used to compute the following alpha diversity indices: Shannon diversity index ( H ) [ 30 ], whose value usually ranges between 1.5 and 3.5 and often does not exceed 4 [ 31 ]; Margalef index ( D ) for species richness (higher the value the greater is the richness) [ 32 ]; Buzas and Gibson evenness index ( E ) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…This could suggest that the Italian hare utilises the food resources according to their availability, preferring the most abundant ones 57 . For example, Fabaceae and Poaceae , although were ingested at high frequency both during the SS and the AW seasons (Supplementary Table S1 ), were consumed further during their full flowering phase 33 , 58 , 59 . Furthermore, the SS diet showed higher richness than the AW one (Table 3 ), probably according to higher plant availability in this season.…”
Section: Discussionmentioning
confidence: 99%